Hudožestvennyj stil’ v istorii ukrainskovo literaturnogo âzyka - Sûta, Galina M. (Stylistyka, 2019)
In the article, the role of the artistic style as one of the major componens of the Ukrainian linguo-culture has been stressed. The writers’ language-creative practice has been qualified as an important factor in the national literary language development and as a criterion of the literary norm formation. As for the latter, two major kinds of writers’ impact are noted – structural-expanding and cutting, aimed at improvement. In this context, the concept of norm arises as an actual parameter to determine the level of correlation of both literary language and language of fiction.